INVENTARISASI EKTOPARASIT PADA KEPITING BAKAU (Scylla serrata) YANG DIBUDIDAYAKAN DI DESA GAMPONG BLANG KOTA BANDA ACEH - Muliyana, Agusriati; Rahmayanti, Fitria; Lubis, Friyuanita (JURNAL AKUAKULTURA, 2022)
Ectoparasite infection has been known as one of the obstacles in crab cultivated. One of best solution to resolves this problem is use an inventory of ectoparasites in cultivated commodities. This study aims to identify the type, intensity level and prevalence of ectoparasite infection in mangrove crabs cultured in Gampong Blang Village, Banda Aceh City. The study was conducted from February to March 2022. A total of 20 samples of mud crab were collected from cultivators in Gampong Blang Village. Furthermore, ectoparasites were observed on the external organs of the samples under microscope. The results showed that two types of ectoparasites were found in the samples, namely Octolasmis sp. and Tricodina sp. The highest prevalence and intensity of ectoparasites was Octolasmis sp. with a prevalence value of 75% and an intensity of 3.67 ind/head. Water quality parameters measured during sample collection were temperature 32.6oC, pH 7.3, salinity 25.6 ppt and dissolved oxygen (DO) 5.2 mg/L.